Genetic Variants Flanking the FGF21 Gene Were Associated with Renal Function in Chinese Patients with Type 2 Diabetes. (7th May 2019) - Yu, Weihui; Zhu, Hong; Chen, Xiong; Gu, Xuejiang; Zhang, Xingxing; Shen, Feixia; Jia, Weiping; Hu, Cheng
Abstract : Aims . Fibroblast growth factor 21 (FGF21) is closely linked with metabolic disorders including diabetes. Evidences suggested that FGF21 may play a protective role against diabetic kidney disease (DKD). However, the relationship between genetic variants in the FGF21 gene region and DKD remains unknown. In our study, we aimed to investigate the association of genetic variations in this gene region with DKD and DKD-related clinical traits. Materials and Methods . We recruited 1340 Han Chinese participants with type 2 diabetes, including 596 DKD patients and 744 patients who was diagnosed with diabetes for more than 5 years but did not progress to DKD. Three single-nucleotide polymorphisms were selected (rs2071699, rs838136, and rs499765) and genotyped. The association between these SNPs and DKD as well as DKD-related quantitative traits was analyzed. Results . We did not find any significant association between these SNPs and susceptibility to DKD in the present study. However, a significant association with estimated glomerular filtration rate (eGFR) was detected: in the non-DKD group, rs838136 was significantly associated with eGFR under an additive model (β = 0.013 ± 0.006, P = 0.0295, β was calculated for log10 eGFR) as well as a recessive model (P = 0.0385 ) and rs499765 was associated with eGFR under a dominant model (P = 0.0411 ) and in the DKD group, rs499765 showed a trend toward association with eGFR under an additive model (β = − 0.022 ± 0.012, P = 0.0820, β was calculated for log10 eGFR) and showed a significant association with eGFR under a dominant model (P = 0.0182 ). Conclusions . Our findings indicated that genetic variations adjacent to FGF21 were associated with eGFR in Chinese diabetic patients.